Decreased expression and aberrant methylation of RASSF5A correlates with malignant progression of gastric cardia adenocarcinoma. Issue 12 (24th November 2014) - Han, Lijie; Dong, Zhiming; Wang, Cong; Guo, Yanli; Shen, Supeng; Kuang, Gang; Guo, Wei
<x xml:space="preserve">Abstract</x> Due to alternative splicing and differential promoter usage, RASSF5 exists in at least three isoforms, RASSF5A, RASSF5B, and RASSF5C. Expression and epigenetic inactivation of different transcripts of RASSF5 in gastric cardia adenocarcinoma (GCA) progression have not been evaluated. Quantitative real‐time RT‐PCR and immunohistochemistry (IHC) methods were used respectively to detect the role of RASSF5A, RASSF5B, and RASSF5C in 132 GCA cases and BS‐MSP method was used to clarify the critical CpG sites of RASSF5A. Expression of RASSF5A and RASSF5C transcripts were easily detectable in all normal gastric cardia epithelial tissues; however, expression of RASSF5B was rare detected in normal gastric cardia epithelial tissues and tumor tissues. Both RASSF5A and RASSF5C expression were frequently downregulated in GCA tumor tissues and RASSF5A was more commonly down‐regulated compared to RASSF5C. Abnormal reduction of RASSF5A was more commonly observed in advanced stage and poor differentiated tumors. The methylation frequency of CpG island 1 region of RASSF5A in GCA tumor tissues was significantly higher than that in corresponding normal tissues and was inversely correlated with RASSF5A expression. Aberrant promoter methylation of RASSF5C was not found in GCA. RASSF5A methylation and protein expression were independently associated with GCA patients' survival. These results indicate that down‐regulation of RASSF5A and RASSF5C expression is a tumor‐specific phenomenon and RASSF5A may be a more common target for inactivation in GCA. Inactivation of RASSF5A through CpG island 1 methylation may play an important role in GCA carcinogenesis and may serve as a prognostic biomarker for GCA. © 2014 Wiley Periodicals, Inc.